Scholars as craftsmen and intensification of work in university - Soria, Sidartha; Gomes, Darcilene Claudio (Canadian journal of Latin American and Caribbean studies, 2022)
This paper aims to study the precariousness of labor among professors in Brazilian universities. To do so, it will emphasize a particular aspect of precariousness: the precariousness of the time of labor. Besides, the analysis encompasses Richard Sennett's theory about craftsman and craftsmanship. In this regard, it suggests the consideration of teaching as a job and, as such, exhibiting typical features thereof, such as methodical curiosity, material consciousness of the activity and permanent self-involvement in its improvement. Given the nature of teaching, it suggests the hypothesis that the phenomenon of precariousness of labor affects teaching, distorting its original nature (the search for academic excellence as fundamental motivation of the professor) and using it even to enhance the very movement of precariousness of university work.